Beyond Viral: A Systematic Review of Indonesia’s Creative Economy in the Shadow of Digital Algorithms - Brilian, Vinsent; Prasetyo, Heru Eko (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2026)
The growth of the creator economy in Indonesia has increased rapidly over the past decade with the development of digital platforms such as YouTube, TikTok, and Instagram. However, global literature on the creator economy has not discussed the characteristics of Indonesian creators, including platform algorithm factors, local monetization strategies, and differences in national audience behavior. This study employs a Systematic Literature Review (SLR) method based on Kitchenham’s 2004 guidelines and PRISMA 2020 to identify patterns of relationships between algorithms, monetization, and the income of Indonesian creators. The literature search was conducted through Scopus, Google Scholar, IEEE Xplore, and ScienceDirect, with a total of 56 articles found; after the PRISMA selection process, 22 articles were further analyzed. The results show that the income of Indonesian creators differs from global patterns, being dominated by MSME endorsements, affiliate marketplaces, and live commerce. In addition, platform algorithms have a major influence on content reach fluctuations, especially for small-to-medium creators with limited digital literacy. Indonesia’s digital culture, local audience preferences, and high consumption of viral content are unique components of the national creator ecosystem. This study makes a significant contribution by filling a gap in global literature that has not yet discussed the characteristics of Indonesian creators in depth